2016
DOI: 10.1016/s2352-3018(16)30054-6
|View full text |Cite
|
Sign up to set email alerts
|

Weekends-off efavirenz-based antiretroviral therapy in HIV-infected children, adolescents, and young adults (BREATHER): a randomised, open-label, non-inferiority, phase 2/3 trial

Abstract: SummaryBackgroundFor HIV-1-infected young people facing lifelong antiretroviral therapy (ART), short cycle therapy with long-acting drugs offers potential for drug-free weekends, less toxicity, and better quality-of-life. We aimed to compare short cycle therapy (5 days on, 2 days off ART) versus continuous therapy (continuous ART).MethodsIn this open-label, non-inferiority trial (BREATHER), eligible participants were aged 8–24 years, were stable on first-line efavirenz with two nucleoside reverse transcriptase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 23 publications
0
37
1
Order By: Relevance
“…An example might be intolerance to study drug treatments due to mild side effects such as nausea or rash, which cause enough discomfort to affect adherence but not the outcome of the disease 1415. By contrast, non-adherence can be driven by factors that influence the study outcome, such as disease severity 1617. For example, consider an open label study where more severely ill patients are more likely not to adhere to the experimental treatment and these patients cross over to the standard-of-care control arm.…”
Section: Implications Of Non-adherence In Non-inferiority Trialsmentioning
confidence: 99%
“…An example might be intolerance to study drug treatments due to mild side effects such as nausea or rash, which cause enough discomfort to affect adherence but not the outcome of the disease 1415. By contrast, non-adherence can be driven by factors that influence the study outcome, such as disease severity 1617. For example, consider an open label study where more severely ill patients are more likely not to adhere to the experimental treatment and these patients cross over to the standard-of-care control arm.…”
Section: Implications Of Non-adherence In Non-inferiority Trialsmentioning
confidence: 99%
“…Working across 11 countries (including one centre in Uganda), this trial compared virological control of short‐cycle therapy (five days on: two days off) with continuous EFV‐based ART in 199 children and young people (aged 8 to 24) (70 from Uganda) living with HIV with viral load <50 c/mL to examine adaptation, acceptability and experience of short‐cycle therapy to inform intervention development 17, 33. The social science component was not fully funded within the trial funding, and a parallel grant from a different funder was secured by the social scientists to support the qualitative research in Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…These findings informed the way in which the final trial findings were reported and could provide valuable input for further research. It should be noted that while some of the qualitative study findings were integrated into the “main” trial paper the paper 17 detailing the qualitative findings (which was submitted at the same time as the main trial findings paper) was not accepted for publication. The qualitative findings paper was published later in a different journal 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial design to test having the weekends off treatment was informed by anecdotal evidence suggesting that managed interruptions can ameliorate the challenges of adhering continuously. 14 The qualitative study aimed to explore the experiences of SCT, and of treatment and care more generally, among a sample of trial participants (aged 10-24). SCT is a behavioural intervention relying on self-administered ART and self-reported adherence.…”
Section: Although Littlementioning
confidence: 99%